Pengaruh Material Bangunan Terhadap Kenyamanan Pengguna Dalam Cerpen In Coeli Quies Karya Lidwina Ika - Hanifah Dian Pertiwi; Salmannisa Yumna Nur Safitri; Eva Dwi Kurniawan (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
A short story or short story is a literary work that tells the main character of an event and is packaged into a dense story. In the short story entitled "In Coeli Quies" by Lidwina Ika, it tells how home is heaven, where heaven is described as a place that is pleasant, calming, happy, full of friendliness, inspiring and enthusiastic. However, the house owned by the main character does not reflect heaven. In this house, users actually feel less comfortable because it is influenced by the inappropriate choice of building materials. The aim of this research is to describe the building materials contained in the literary work entitled "In Coeli Quies" by Lidwina Ika. The problem raised is how building materials can affect user comfort as seen in the short story. This research method uses a qualitative descriptive method with a hermeneutic approach which is intended as a process of changing something or a situation of ignorance into understanding. The findings obtained show that when a building uses walls made of brick and roof coverings using spandex, the function of the building is used as a residence. So the results obtained in terms of comfort obtained by users are very poor.